Development of Socialist Democracy and Internationalization of Public Life of Socialist Nations - Zimanas, Genrikas (Problemos, 1976)
Further development of socialist democracy is one of the basic features and objectives of developed socialism. It is determined by an intensive growth of the productive forces and improvement of productive relations. Its objective is the constant participation of citizens in state administration. Soviets, trade unions, state administration, working people’s collectives are the decisive factors in developing socialist democracy. The CPSU is the guiding force in this process of democratization. International relations constitute one of the forms of socialist democracy. The development of socialist democracy determines the internationalization of social life. The latter is subject to the main principle of socialist democracy – democratic centralism – which allows to take into account both particular and general features in the development of our multinational state.